EFFECT OF LEAF EXTRACT ON STYLET BEARING NEMATODES AND ON GROWTH PARAMETERS OF Two WHEAT VARIETIES (Biological Sciences - PJSIR, 2002)
Leaf extracts from Azadirachta indica, Nicotiana tabacum and Euca lyptus citriodora were tested for their nematicidal effect on Helicotylenchus indicus, Bitylenchus gojfarti and Pratylenchus thomei and on growth and yield of Pavon-76 and Mehran wheat varieties in microplots. All  the amendments  significantly  reduced  the population  of the nematodes. Average  weight of shoot, root and yield  were increased  by A.  indica treatment.  Nicotiana  tabacum increased  the yield  in variety Pavon-76.